The right to legal representation of an accused person; existence, application and limitation: a comparison study between Malaysia and The United States / Dalira Din ...[et al.] - Din, Dalira; Leman, Shahidah Nafisah; Abdul Rahim, Salwa Asmary; Ismail, Wan Muhammad Faizal (2006)
This research is carried out to discover the reality of the practice of the right to legal representation of an accused person in Malaysia and to compare with the United States of America. The main objective is to know in reality whether this right is given absolutely and is there any limitation by the authority in any cases. The accused person has the right under Article 5 of the Federal Constitution. The problem here is that when the accused person being detain without the aid of counsel. The detainee often being humiliated and abuse by the police so that the accused will confess or plead guilty thus, there is no use to proceed to the court as statement had been made and the accused had plead guilty. In contrast, this right must be subject to certain necessary limitations in order to prevent any undue interference with the course of investigation. The police must support and prove that their action is in good faith. The United States government provides the right to counsel in most cases and to deny it will make the court to loss its right and jurisdiction to proceed with the case. The right to legal representation will remain unless the accused himself waived the rights. As a conclusion, the application in Malaysia and the United States is diverse although the law is quite same. One similarity is that this right will be given subject to the court and the police discretion.